Optimization of light hydrocarbon recovery system in condensate gas field. (November 2019) - Lu, Hongfang; Ma, Guoguang; Cao, Lianjin; Azimi, Mohammadamin
Abstract: During the middle and later stages of condensate gas field development, the flow rate and pressure of the light hydrocarbon recovery system gradually decrease, and there is a certain deviation between the design parameters and the actual operation parameters of the equipment, resulting in a decrease in the recovery rates of propane ( C 3 ) and higher hydrocarbons ( C 3 + ). Therefore, it is necessary to optimize the system to obtain greater economic value. In order to solve this problem, the paper analyzes the sensitivity of the equipment operating parameters based on the sequential-modular method. The black box model is used to analyze the equipment and the whole system, and the subsystem with large exergy loss is found. Moreover, this paper optimizes the light hydrocarbon recovery system using parameter optimization and process optimization, and compares the results. According to the analysis, the main conclusions are drawn: (1) The outlet pressure of expander and the temperature of deethanizer bottom have great influence on the light hydrocarbon recovery system, the reduction of the expander outlet pressure from 2.3 MPa to 1.8 MPa can increase the recovery of C 3 by 5%. Decreasing the bottom temperature of the deethanizer from 80 ∘ C by 20 ∘ C can increase the recovery of C 3 by 9.2%. (2) Optimized process using direct heat exchange technology has a better optimization effect than the parameter optimization process, the C 3 recovery of the optimized system increased by 19.1% to 93%, the recovery of C 3 + increased by 14.4% to 95%.